The Effect of Product Quality, Store Atmosphere, and Promotion on Purchase Decisions at Hagaa Coffee Shop Malang - NOPENDRA; Rahmad Wijaya; Sri Nastiti Andharini (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to analyze the effect of product quality, store atmosphere, and promotion on purchasing decisions at Hagaa Coffee. As for the background of this writing because of the emergence of many cafe businesses in the city of Malang. This study uses a quantitative descriptive approach. Data were collected through an online survey with a non-probability method of purposive sampling using a questionnaire instrument. Respondents are consumers who have made transactions at Hagaa coffee within the last 3 months totaling 100 respondents. The data analysis technique used is the multiple linear analysis techniques. The results of regression analysis show that product quality, store atmosphere, and promotions have a significant partial and simultaneous effect on consumer purchasing decisions at Hagaa Coffee Malang and product quality has the most dominant influence on purchasing decisions.